Translational Inhibition of CTX-M Extended Spectrum β-Lactamase in Clinical Strains of Escherichia coli by Synthetic Antisense Oligonucleotides Partially Restores Sensitivity to Cefotaxime - Readman, John B.; Dickson, George; Coldham, Nick G. (Frontiers in Microbiology, 2016)
Synthetic antisense oligomers are DNA mimics that can specifically inhibit gene expression at the translational level by ribosomal steric hindrance. They bind to their mRNA targets by Watson Crick base pairing and are resistant to degradation by both nucleases and proteases. A 25 mer phosphorodiamidate morpholino oligomer (PMO) and a 13 mer polyamide (peptide) nucleic acid (PNA) were designed to target mRNA (positions -4 to +21, and –17 to –5 respectively) close to the translational initiation site of the extended spectrum β lactamase resistance genes of CTX M group 1. These antisense oligonucleotides were found to inhibit β lactamase activity by up to 96% in a cell free translation transcription coupled system using an expression vector carrying a blaCTX-M-15 gene cloned from a clinical isolate. Despite evidence for up regulation of CTX-M gene expression, they were both found to significantly restore sensitivity to cefotaxime in E. coli AS19, an atypical cell wall permeable mutant, in a dose dependant manner (0 - 40 nM). The PMO and PNA were covalently bound to the cell penetrating peptide (KFF)3K and both significantly (P<0.05) increased sensitivity to cefotaxime in a dose dependent manner (0 - 40 nM) in field isolates harbouring CTX-M group 1 β-lactamases. Antisense oligonucleotides targeted to the translational initiation site and Shine Dalgarno region of blaCTX-M-15 inhibited gene expression, and when conjugated to a cell penetrating delivery vehicle, partially restored antibiotic sensitivity to both field and clinical isolates.